Videogames as an 'Unheroic' Medium: The Child Hero's Journey. Issue 5 (July 2023) - Reay, Emma
In this article, I examine two contemporary videogames that engage critically and imaginatively with conventional definitions of heroism. In Röki (Polygon Treehouse) and Knights and Bikes (Foam Sword Games), the child-avatars loosen the connection between maturity and self-reliance by framing interdependence as both an inevitable and a desirable condition of human society. Furthermore, by emphasizing children's supposed malleability, these games insist on the relationality of identities: they suggest that one's identity depends on the interactions one has with individuals and institutions. I suggest that by centering cooperation, these games destabilize myths of independence and autonomy that surround the lone hero of hyper-individualism and thereby challenge assumptions about the kinds of heroism videogames can portray.